Dental aesthetics and self-esteem of patients seeking orthodontic treatment - Wan Nurazreena, Wan Hassan
Abstract: (1) Objective: To investigate how patients' perceptions of their dental aesthetics and their sense of self-esteem are related; (2) Methods: This cross-sectional survey recruited 141 new patients seeking orthodontic treatment. Patients completed a self-administered questionnaire consisting of three parts; the Malaysian Psychosocial Impact of Dental Aesthetics Questionnaire (M-PIDAQ), Rosenberg Self-esteem Scale (RSES-M) and Aesthetics Component of the Index of Or-thodontics Treatment Need (IOTN-AC). Clinical assessment comprised the Dental Health Com-ponent of the Index of Orthodontics Treatment Need (IOTN-DHC). Multiple linear regression was performed with self-esteem as the dependent variable while the independent variables com-prised the domains of PIDAQ, IOTN-AC, IOTN-DHC and patients’ demographics such as age, gender and their level of education; (3) Results: The response rate was 96.5% (n = 136 respond-ents). The multiple linear regression found, when the other predictors in the model are held con-stant, Social Impact, Aesthetic Concern, and Dental Self-Confidence are the factors that signifi-cantly contributed to explaining the variation in self-esteem, accounting for, 3.9%, 2.3%, and 2.0%, respectively. The entire model explained 23% of the variation in self-esteem; (4) Conclusions: The psychosocial impact of aesthetics appeared to influence the self-esteem of orthodontic treat-ment-seeking patients.